Ethylene polymerization using immobilized fluorine-containing bis-salicylidenimine-titanium complexes - Gagieva, S. Ch; Tuskaev, V. A.; Takazova, R. U.; Buyanovskaya, A. G.; Smirnova, Olga V.; Bravaya, N. M.; Bulychev, B. M. (Russian Chemical Bulletin, 2019)
A fluorine-containing bis-salicylidenimine-titanium(iv) complex TiCl2η2-1-[C(H)=NC6F4]-2-O-Ph(But)22 has been synthesized and immobilized on silica gel, polysorb, and magnesium chloride. The catalytic properties of heterogenized complexes activated by organoaluminum compounds (OAC) have been studied in ethylene polymerization. it has been demonstrated that the activity of the catalytic systems obtained by simultaneous immobilization of the complex, OAC, and [Me2NHPh]+[B(C6F5)4]− is an order of magnitude higher than in the absence of perfluorophenylborate. Catalysts on inorganic supports exhibit higher activity than catalysts on polymer supports. The use of anhydrous magnesium chloride as a support makes it possible to obtain a highly efficient catalyst for the synthesis of ultrahigh molecular weight polyethylene (activity up to 1350 (kg of polymer) (mol Ti h atm)−1, melting point 140–143 °C).
CRIS-Team Scopus Importer:2023-04-20
Keywords: catalysis; ethylene; polymerization; titanium complex